Analysis of the Impact of Financial Technology (Fintech) on the Needs of Generation Z in the Community Around UPI Purwakarta Campus - Zahratunnisa, Zahratunnisa; Sari, Dian Permata; Hikmawan, Rizki (Dinasti Publisher, 2024)
In the era of technological acceleration, technological advancements affect various aspects of life including the financial sector. Financial Technology (fintech) is an innovation that facilitates financial transactions and online loans, especially for generation Z. However, this convenience is also accompanied by risks such as fraud and consumptive behavior. This study aims to determine the impact and factors that affect Generation Z in financial technology in the community around the UPI Purwakarta campus. The research method used was a quantitative research method with a likert scale and distributed to 435 respondents. The data analysis techniques used are correlation analysis and simple regression analysis. While the hypothesis test uses the determination coefficient and the F test. The results of this study show that there is a significant (simultaneous) influence between the perception of Generation Z and the use of fintech applications and the magnitude of the influence is 31.1%.